Nilai Keanekaragaman Hayati Perikanan dengan Mengadopsi Kriteria OECM : Studi Kasus PAAP Teluk Kolono, Sulawesi Tenggara - Siregar, Amelia Fransiska; Adrianto, Luky; Zairion, Zairion (Universitas Diponegoro, 2025)
Fisheries Access Area Management Area (PAAP) of Kolono Bay as a connector, interaction relationship and ecosystem balance. This study aims to assess fisheries biodiversity using the Other Effective Area-Based of Conservation Measures (OECM) criteria for the Fisheries Access Area Management Area (PAAP) of Kolono Bay. Interview methods, Focus Group Discussion (FGD) were analyzed using Social Ecological Network Analysis (SENA), and biodiversity values. The results showed that the Social-Ecological System (SES) network in the PAAP of Kolono Bay contained a connectivity system of 27 components (nodes) and 46 relationships (edges). Resources Unit (RU) is an important variable in influencing the ecosystem of the resource system. In addition, fisheries biodiversity in this area showed a low value with a total of 17 families and 64 species found. The diversity and uniformity values were in the medium to high category, while dominance was in the low category or none dominated. The utilization status is obtained in 3 categories including: Least Concern (LC), Vulnerable (VU), and Not Evaluated (NT). The utilization status of less concern (LC) is more dominant indicating that the fish community in the area is considered not endangered. Keberadaan Pengelolaan Area Akses Perikanan (PAAP) Teluk Kolono sebagai konektivitas, hubungan interaksi dan keseimbangan ekosistem. Penelitian ini bertujuan untuk menilai keanekaragaman hayati perikanan dengan mengadopsi kriteria Other Effective Area-Based of Conservation Measures (OECM) terhadap kawasan Pengelolaan Area Akses Perikanan (PAAP) Teluk Kolono. Metode wawancara, Focus Group Discussion (FGD) dIanalisis menggunakan Social Ecological Network Analysis (SENA) , dan nilai biodoversitas. Hasil penelitian menunjukkan bahwa jejaring Sistem Sosial-Ekologi (SES) di PAAP Teluk Kolono terdapat konektivitas sistem sebanyak 27 komponen (node) dan 46 hubungan (edge). Resources Unit (RU) merupakan variabel penting dalam mempengaruhi keberlanjutan jejaring sistem sumberdaya. Selain itu, keanekaragaman hayati perikanan di kawasan ini mengindikasi nilai kelimpahan rendah dengan total 17 famili dan 64 spesies yang ditemukan. Nilai keaenakaragman dan keseragaman dalam kategori sedang sampai tinggi, sedangkan dominansi masuk kategori rendah atau tidak ada yang mendominasi. Status pemanfaatan didapatkan 3 kategori diantaraya : Least Concern (LC), Vulnerable (VU), dan Not Evaluated (NT). Status pemanfaatan least conern (LC) lebih mendominasi mengindikasikan bahwa komunitas ikan di kawasan dianggap tidak teranam kepunahan.